THE EVALUATION OF COUNSELING AND GUIDANCE SERVICES BASED ON TEACHER VIEWS AND THEIR PREDICTION BASED ON SOME VARIABLES - Yuksel-Sahin, Fulya (ESKISEHIR OSMANGAZI UNIV, FAC EDUCATION, 2009)
This study evaluated psychological counseling and guidance services based on elementary and secondary education teachers' views. Participants were 204 teachers. School Guidance Services Scale and Teacher Personal Information Form were used for gathering the necessary information. Percentage calculations and multiple regression analysis were used for data analysis. The results showed that teachers listed the guidance services from the most utilized to the least as follows: consultation, counseling, information gathering and outreach, appraisal, orientation, placement, research and evaluation public and family relations and follow-up services. Results of this study showed that overall an approximately 46% of all counseling and guidance services were offered. Moreover, according to the results of the study, the grade being taught and holding the view that schools should definitely have a school counselor were significant predictors of teachers' evaluation of counseling and guidance services. However, taking counseling and guidance lessons during undergraduate studies, the length of service and gender were not significant predictors of teachers' evaluation of counseling and guidance services.
Keywords: counselling and guidance services; teacher; education; guidance; Education & Educational Research